Implementing Service-Learning Programs in Physical Education; Teacher Education as Teaching and Learning Models for All the Agents Involved: A Systematic Review - Pérez-Ordás, Raquel; Nuviala, Alberto; Grao-Cruces, Alberto; Fernández-Martínez, Antonio (International journal of environmental research and public health, 2021)
Service-learning (SL) is the subject of a growing number of studies and is becoming increasingly popular in physical education teacher education (PETE) programs. The objective of this study was to conduct a systematic review of the implementation of SL programs with PETE students. The databases used were Web of Science, SPORTDiscus (EBSCO), and SCOPUS. Articles were selected on the basis of the following criteria: (a) published in a peer-reviewed journal; (b) covers the use of SL programs with PETE students; (c) relates to physical education or physical activity programs; (d) availability of a full-text version in English and/or Spanish. Thirty-two articles met the inclusion criteria. Two types of findings were observed: firstly, findings relating to the study characteristics and objectives and, secondly, recommendations for improvement of this type of intervention. The objectives of the different studies focused on (a) the impact of the SL methodology on PETE students’ professional, social, and personal skills; (b) its impact on the community; (c) analysis of the effectiveness and quality of the programs. All but two studies analyzed the impact of SL on PETE, while only four analyzed community participants and only three analyzed the quality of the SL program. Recommendations for improving SL programs used with PETE students included: all stakeholders, e.g., students and community participants, should be studied and coordinated; the quality of the programs should be assessed, as studying the effectiveness of SL programs could help to attain the objectives of both students and the community; mixed methods should be used; and intervention implementation periods should be extended to provide more objective, controlled measurements.